Radioactive waste fuels next-generation reactors. (Research'eu results magazine)
Recycling of nuclear waste can enhance the sustainability and safety of nuclear power production. Scientists have developed techniques to decrease the long-term radioactivity of waste by reusing it in next-generation reactors.